Answer:
S' (1,-2)
S'' (0,0)
Step-by-step explanation:
Answer:
Correct Answer is C(−5 ±square root 6)
Step-by-step explanation:
2x^2+20x+38=0
2(x^2+10x+19)=0
x^2+10x+19=0
This is a quadratic equation here we have used following formula to find the roots of this equation
x=-b−±square root (b^2-4*a*c))/2*a......(1)
Here,
a=1
b=10
c=19
put values of a, b and c in equation (1)
x=(-10 ±square root(10^2-4*1*19))/2*1
x=(-10 ±square root(100-76))/2
x=(-10 ±square root(24))/2
x=(-10 ±square root(2*2*6))/2
x=(-10 ±2square root(6))/2
x=2(-5 ±square root(6))/2
x=-5 ±square root(6)
Hope this answer will help you
The expression is
See
Its distributive property which states that
Option A